INTERFERENCE IN THE WHATSAPP GROUP OF INDONESIAN LANGUAGE AND LITERATURE EDUCATION STUDENTS CLASS OF 2021 AT ROKANIA UNIVERSITY - Nasution, Aisyah Rahmadany; Arianti, Rita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2025)
Interference in the WhatsApp group of Indonesian Language and Literature education students class of 2021 is still often found. This happens so that the writing looks more slangy or even less careful in writing correct Indonesian. However, this causes errors in the real sense, namely interference. Interference can be interpreted as an error that occurs due to the use of two different language codes. This research examines interference because not all Indonesian language and literature education students use Indonesian properly and correctly via the WhatsApp application. The aim of this research is to describe the interference contained in the WhatsApp group of Indonesian Language and Literature Education students class of 2021. This type of research is qualitative research with descriptive methods. The results of this research found 35 interference data with morphological forms. It can be concluded that the 2021 class of PBSI students lack accuracy in writing good and correct Indonesian so that in their use there are many changes, deletions and additions of phonemes. So to reduce the interference that occurs, Indonesian Language and Literature Education students class of 2021 at Rokania University need to understand and be precise in writing correct Indonesian.